(untitled) (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: Microbial burden is a great threat in production, transportation and distribution of poultry feed. E. coli and Salmonella is an important cause of food borne disease in humans throughout the world and is a significant cause of morbidity, mortality and economic loss. Therefore, the present study was designed to isolation of common coliform bacteria from the Poultry feed. Material and Methods: This study was performed as per the standard protocol of microbial analysis of poultry feed to isolate and identify the common pathogen E. coli and Salmonella present in feed sample. Results: Out of 70 samples examined, 62(88.57%) showed growth in which E.coli was 38(61%) and 24(39%) was Salmonella and 16(22.86%) samples showed fair growth and 8(11.42%) samples showed no growth. Conclusion: Most of the poultry feed sample of this area was found to be highly contaminated with E. coli and Salmonella.